2022
DOI: 10.1177/23743735221092628
|View full text |Cite
|
Sign up to set email alerts
|

Missing Persons Alert: Finding the Lost “Person” in Patient-Oriented Research

Abstract: After a decade of attempts at patient-oriented research, this article seeks to advance the approach, making individuals and communities active partners in health research. Patient-oriented research remains inconsistently implemented, tokenistic, and met with resistance—largely due to the system in which it was conceived and practiced. Patients remain bound by object-oriented medical cosmologies, thus reaffirming the hierarchical system underpinned by professional dominance. Until health research and researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…For example, an earlier survey indicated that patients’ experiences with implant services were mainly driven by decisions made by their implant team; 7 another study found that patients had not been given the opportunity to set their own goals or benchmarks 8 . Tellingly, in the latter study, the questionnaire used to interview patients about their rehabilitation was developed by researchers with no input from patients—even as patients consistently indicate their preference to be involved in research and care plans 9–12 …”
Section: Users Weigh Inmentioning
confidence: 99%
“…For example, an earlier survey indicated that patients’ experiences with implant services were mainly driven by decisions made by their implant team; 7 another study found that patients had not been given the opportunity to set their own goals or benchmarks 8 . Tellingly, in the latter study, the questionnaire used to interview patients about their rehabilitation was developed by researchers with no input from patients—even as patients consistently indicate their preference to be involved in research and care plans 9–12 …”
Section: Users Weigh Inmentioning
confidence: 99%
“…This misalignment risks turning a once-radical tool for societal transformation into a subtle form of control, thereby perpetuating the very dynamics it was created to dismantle. If the academic community does not actively uphold the emancipatory principles of participatory research, we risk diluting its potential as an agent of genuine change and reducing it to a tokenistic exercise [ 5 , 16 , 46 , 49 , 63 ].…”
Section: Introductionmentioning
confidence: 99%